No fio da navalha: sentidos das experiências e projetos de futuro de jovens em cumprimento de medida socioeducativa de semiliberdade - Jorddana Rocha de Almeida (2017)
The general objective of this research was to analyze the juvenile condition of young people in situation of liberty restriction, seeking to understand the meanings they attributed to the experiences of the socio-educational measure of semi-liberty and their future projects. The theoretical and methodological framework is anchored in the Sociology of Youth and the Sociology of Experience. Youth is approached as a social condition and a type of representation in which young people are perceived as subjects of rights, andas singular, social and multiple beings. The research was carried out in a Semi-liberty House in Governador Valadares-MG. It is a qualitative study, developed by different methodological instruments: document analysis, participant observations and semi-structured interviews with 16 young people between 13 and 18 years old. . Nine young people were interviewed according to the period of stay in the unit during the field research, time of compliance of the measure, different trajectories, postures in relation to the experiences of the semi-freedom and age. The youths' condition of the young and their multiple dimensions constituted a sociocultural context of vulnerability, of unjust, oppressive and violent social relations in the perspective of the violation of social rights and dehumanization processes. The occurrences of the socio-educational measure of semi-freedom were experienced as challenging, demarcated by intra and intergenerational conflicts, seen by the participants as test situations and constant proof. The analysis indicated that the young people surveyed lived in permanent tragic and borderline situations. They fueled the desire to emerge from the contravention, stimulated or forced by the socio-educational system and by the families, but at the same time, they saw no prospect of breaking ties and commitments to the world of crime. They were always on the borderline between the world of measurement and the illicit world. The relation with the dimension of the project of the future was established by the youth in a very distant way, prevailing an adhesion to the present time. In this way, the meanings of experiences were also marked by ambiguities.